1984
DOI: 10.1017/s0022143000006250
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity Soundings of Glacier Beds: A Test Study on Grubengletscher, Wallis, Swiss Alps

Abstract: ABSTRA CT . Elec tri cal res isti vity sounding, usin g electrodes whic h are lowered direc tl y to th e ice-rock interface in bore holes, is proposed as a technique for stud ying the exact position of glacier beds, as well as their lithologica l ch a rac teristics. A test study is d escribed on G rubeng letscher, a pa rtially cold Alpin e glacier in Switzerl a nd. Res ul ts of so undings a long a 400 m long p rofil e indicate that previo us depth determina ti o ns, based on radio echo -soundings, were in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Concerning direct ice thickness measurements, GPR had started to replace earlier seismic soundings (cf., for instance Haeberli and Fisch [1984] and Narod and Clarke [1994]) and is now widely used [cf. Farinotti , 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning direct ice thickness measurements, GPR had started to replace earlier seismic soundings (cf., for instance Haeberli and Fisch [1984] and Narod and Clarke [1994]) and is now widely used [cf. Farinotti , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…A critical step for the use of modeled glacier beds in other applications is the assessment of their quality, which requires validating them with ground truth data. For still existing glaciers, bedrock information can be derived from (hot‐water) drilling, geophysical soundings like ground penetrating radar (GPR) or – optimally – a combination of both [ Haeberli and Fisch , 1984]. Such reference information, however, is only sparsely available and in many cases biased toward crevasse‐free, flat and thus thick glacier parts with compressing flow [e.g., Frey et al , 2010].…”
Section: Previous Work On Glacier Thickness Modelingmentioning
confidence: 99%
“…The presence of such sediments can be confirmed, their extent and thickness mapped, and hydromechanical changes within them detected, using borehole-based electrical resistivity soundings and SP measurements (e.g., Haeberli and Fisch, 1984;Brand et al, 1987;Engelhardt et al, 1990;Blake and Clarke, 1999). Kulessa et al (2003aKulessa et al ( , 2006b demonstrated that a combination of automated subglacial SP measurements and mathematical modelling together with 3-D inversion of time-lapse subglacial electrical resistivity data allows comprehensive characterisation of the hydraulic properties of and processes within subglacial sediments.…”
Section: Glacier and Snow Hydrologymentioning
confidence: 99%
“…Their aim was to examine the anisotropy, temperature, and density structure of the ice shelf and to infer conditions at the lower boundary where ice and seawater are in contact. More recently, Haeberli and Fisch [1984] and Brand et al [1987] have placed electrodes in boreholes in order to measure the resistivity of the glacier bed.…”
Section: Introductionmentioning
confidence: 99%